George Sabin Gibbs papers - Gibbs, George Sabin, 1875-1947.
Correspondence, field notebook (1898-1899), telegrams, reports, memoranda, military records, clippings, printed material, and other papers chiefly concerning Gibbs's career leading up to his appointment as U.S. Army chief signal officer in 1928. Includes papers relating to his service in the Philippines during the Philippine American war, 1899-1902, and in Cuba during the American occupation, 1906-1909. Also includes correspondence relating to his career with International Telephone and Telegraph Corporation and Postal Telegraph-Cable Company. Correspondents include Sosthenes Behn, Dwight Filley Davis, Adolphus W. Greely, William Mitchell, Edgar Russel, and Jonathan Mayhew Wainwright.
In part, photocopies.
Library of Congress Geography and Map Division.
Businessman and U.S. Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Behn, Sosthenes, -- 1882-1957 -- Correspondence; Davis, Dwight Filley, -- 1879-1945 -- Correspondence; Greely, A. W. -- 1844-1935 -- Correspondence; Mitchell, William, -- 1879-1936 -- Correspondence; Russel, Edgar, -- 1862-1925 -- Correspondence; Wainwright, Jonathan Mayhew, -- 1883-1953 -- Correspondence; United States. -- Army. -- Signal Corps; International Telephone and Telegraph Corporation; Postal Telegraph-Cable Company; Cuba -- History -- American occupation, 1906-1909.; Philippines -- History -- Philippine American War, 1899-1902.; Army officers; Businessmen